2009
DOI: 10.1243/13506501jet666
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical analysis of an infinitely wide rigid cylinder rotating over a grooved surface in hydrodynamic conditions

Abstract: A theoretical model that evaluates the frictional properties of an infinitely wide rigid cylinder rotating over a grooved surface in a hydrodynamic lubrication regime is presented in this article. The parabolic approximation of the film thickness is used in order to analytically compute the pressure distribution in the fluid film. At the discontinuities of the grooved surface, the conservation of the flowrate is applied. The pressure distribution was also computed using a commercial CFD software. Different gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
(11 reference statements)
0
7
0
1
Order By: Relevance
“…10 Marian et al. 11 established a theoretical model of the textured surface of an infinitely wide rigid shaft, and introduced the boundary conditions of Jakobsson–Floberg–Olsson (JFO), and then analyzed the influence rules of the texture surface on the rigid rotation axis. Yu 12 established a numerical model for cylindrical dimples, showed that the depth-to-diameter ratio and area ratio of micro-dimples were the important factors that affected the surface lubrication properties of textured surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Marian et al. 11 established a theoretical model of the textured surface of an infinitely wide rigid shaft, and introduced the boundary conditions of Jakobsson–Floberg–Olsson (JFO), and then analyzed the influence rules of the texture surface on the rigid rotation axis. Yu 12 established a numerical model for cylindrical dimples, showed that the depth-to-diameter ratio and area ratio of micro-dimples were the important factors that affected the surface lubrication properties of textured surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] The main mechanism of the effect of surface microdimple structure on the friction performance of the friction pairs is shown with regard to three aspects: under the condition of fluid lubrication, the microdimple structure can effectively produce hydrodynamic lubrication effects; under the condition of mixed friction, micro-dimples can be used as microoil tanks to make lubrication more effective; the worn abrasive particles can be stored effectively, and the occurrence of second wear can be reduced under the condition of boundary lubrication and dry friction. 8,9 With regard to the theoretical simulation calculation, the influences of different texture shapes including rectangles, circles, triangles on the working performance of journal bearing were researched based on the Reynolds equation by Rahmani et al 10 Marian et al 11 established a theoretical model of the textured surface of an infinitely wide rigid shaft, and introduced the boundary conditions of Jakobsson-Floberg-Olsson (JFO), and then analyzed the influence rules of the texture surface on the rigid rotation axis. Yu 12 established a numerical model for cylindrical dimples, showed that the depth-todiameter ratio and area ratio of micro-dimples were the important factors that affected the surface lubrication properties of textured surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical results were also confirmed by the experimental study of the authors. Jang and Marian et al 12,13 carried out theoretical analysis of journal bearing with a grooved surface, and they found that the parameters of the texturing have significant influences on the stability, load capacity, and tribological characteristics of journal bearing. Sinanog˘lu et al 14 investigated the effects of surface texturing on the load capacity, and the research showed that the trapezoidal texture is better than that of saw.…”
Section: Introductionmentioning
confidence: 99%
“…The research on surface textures can be divided into theoretical and experimental approaches. With the theoretical approach, numerous studies have utilised the Reynolds equation or the Navier-Stokes equations to analyse the mechanism behind textured surfaces [4][5][6][7]. For example, Bai et al [8] numerically investigated partial texturing with elliptical dimples, and the results showed that the orientation of dimples can greatly enhance the hydrodynamic effect.…”
Section: Introductionmentioning
confidence: 99%
“…The research on surface textures can be divided into theoretical and experimental approaches. With the theoretical approach, numerous studies have utilised the Reynolds equation or the Navier–Stokes equations to analyse the mechanism behind textured surfaces [4–7]. For example, Bai et al .…”
Section: Introductionmentioning
confidence: 99%